Emerging roles of intratumoral microbiota: a key to novel cancer therapies - Fang, Pengzhong; Yang, Jing; Zhang, Huiyun; Shuai, Diankui; Li, Min; Chen, Lin; Liu, Liping (Frontiers in Oncology, 2025)
Microorganisms, including bacteria, viruses, and fungi, have been found to play critical roles in tumor microenvironments. Due to their low biomass and other obstacles, the presence of intratumor microbes has been challenging to definitively establish. However, advances in biotechnology have enabled researchers to reveal the association between intratumor microbiota and cancer. Recent studies have shown that tumor tissues, once thought to be sterile, actually contain various microorganisms. Disrupted mucosal barriers and adjacent normal tissues are important sources of intratumor microbiota. Additionally, microbes can invade tumors by traveling through the bloodstream to the tumor site and infiltrating through damaged blood vessels. These intratumor microbiota may promote the initiation and progression of cancers by inducing genomic instability and mutations, affecting epigenetic modifications, activating oncogenic pathways, and promoting inflammatory responses. This review summarizes the latest advancements in this field, including techniques and methods for identifying and culturing intratumor microbiota, their potential sources, functions, and roles in the efficacy of immunotherapy. It explores the relationship between gut microbiota and intratumor microbiota in cancer patients, and whether altering gut microbiota might influence the characteristics of intratumor microbiota and the host immune microenvironment. Additionally, the review discusses the prospects and limitations of utilizing intratumor microbiota in antitumor immunotherapy.